2003
DOI: 10.1111/j.1749-6632.2003.tb05960.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation: One Side of a Larger Picture

Abstract: Hypomethylation signifies one end of a spectrum of DNA methylation states. In most cases hypomethylation refers to a relative state that represents a change from the "normal" methylation level. Hypomethylation, when approached from a topographical perspective, has been used to describe either overall decreases in the methylation status of the entire genome (global hypomethylation) or more localized relative demethylation of specific subsets of the genome, such as the promoter regions of protooncogenes or norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(104 citation statements)
references
References 109 publications
2
100
0
2
Order By: Relevance
“…This phenomena is also not well understood, but may contribute to carcinogenesis by several mechanisms, such as loss of imprinting, chromosomal instability, and reactivation of transposable elements (reviewed in Esteller, 2003). Due to limited space, we are not able to give a more detailed overview about this topic, and we encourage interested readers to refer to other excellent reviews on the connection of DNA methylation and cancer (Dunn, 2003;Jaenisch and Bird, 2003;Laird, 2003;Szyf, 2003).…”
Section: Aberrant Gene Repression and Cancermentioning
confidence: 99%
“…This phenomena is also not well understood, but may contribute to carcinogenesis by several mechanisms, such as loss of imprinting, chromosomal instability, and reactivation of transposable elements (reviewed in Esteller, 2003). Due to limited space, we are not able to give a more detailed overview about this topic, and we encourage interested readers to refer to other excellent reviews on the connection of DNA methylation and cancer (Dunn, 2003;Jaenisch and Bird, 2003;Laird, 2003;Szyf, 2003).…”
Section: Aberrant Gene Repression and Cancermentioning
confidence: 99%
“…Hypomethylation is involved in the progression from the premalignant to a fully developed malignancy (17) and leads to activation of genes important for cancer development. Studies have indicated that overexpression of maspin in gastric, pancreatic, and ovarian cancers results from promoter CpG demethylation (refs.…”
Section: Maspin Gene Regulation Dna Methylation and Histone Methylamentioning
confidence: 99%
“…[12][13][14][15][16][17] Hence remethylation of DNA by condensing the chromatin could prevent or decrease the accessibility of transcription machinery to the DNA, resulting in a decrease in mRNA expression. In support of this conjecture, targretin has been reported to decrease the expression of many more genes than it increased in lung tumors.…”
Section: Discussionmentioning
confidence: 99%